2002
DOI: 10.1139/f01-213
|View full text |Cite
|
Sign up to set email alerts
|

Simplified food webs lead to energetic bottlenecks in polluted lakes

Abstract: Very little is known about the consequence of human activities on the flow of energy through natural ecosystems. Here, we present a trophic-based approach to describing energy relationships in pollutant-disturbed lakes, emphasizing the importance of prey diversity in maintaining energy transfer to growing fish. Both diet and community analysis indicated that the food web leading to yellow perch (Perca flavescens) in metal-polluted lakes was extremely simplified compared with reference lakes. Through the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
3
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 13 publications
3
81
3
1
Order By: Relevance
“…2000; Sherwood et al 2002), intermediary metabolism (Levesque et al 2002), aerobic metabolism (Rajotte and Couture 2002;Audet and Couture 2003;Couture and Kumar 2003), and even basic morphometric condition indicators (Laflamme et al 2000;Levesque et al 2002;Pyle et al 2005;Couture et al 2008b). Although this substantial literature leaves little doubt that metals affect the condition of wild yellow perch, natural variations in fish condition likely confound interpretation of most indicators of yellow perch health.…”
Section: Metal Effects On Condition and Physiology Of Wild Yellow Perchmentioning
confidence: 99%
See 1 more Smart Citation
“…2000; Sherwood et al 2002), intermediary metabolism (Levesque et al 2002), aerobic metabolism (Rajotte and Couture 2002;Audet and Couture 2003;Couture and Kumar 2003), and even basic morphometric condition indicators (Laflamme et al 2000;Levesque et al 2002;Pyle et al 2005;Couture et al 2008b). Although this substantial literature leaves little doubt that metals affect the condition of wild yellow perch, natural variations in fish condition likely confound interpretation of most indicators of yellow perch health.…”
Section: Metal Effects On Condition and Physiology Of Wild Yellow Perchmentioning
confidence: 99%
“…In contrast, RN fish exceeding tissue Cd and Cu concentration thresholds generally expressed higher liver and muscle LDH activities, but exceeding Ni thresholds led to lower liver and muscle LDH activity. Muscle LDH activity in yellow perch has been used as an indicator of activity cost (Sherwood et al 2002;Kaufman et al 2006). Our data indicate that, at least for RN fish, metal contamination must be considered when LDH activity is used as an indicator of locomotion in contaminated yellow perch.…”
Section: Metal Effects On Metabolic Enzyme Activities and Longevitymentioning
confidence: 99%
“…Post and Cucin (1984) showed that predation pressure on littoral benthic invertebrates by introduced yellow perch decreased biomass and body size in benthic invertebrate communities. Many other studies have shown the important interactions between fish and littoral benthic invertebrate communities (Diehl 1992, Carbone et al 1998, Sherwood et al 2002. Fish can be efficient predators and are important in structuring invertebrate communities in aquatic ecosystems ranging from streams (Wooster 1994, Nilsson et al 2008) to tropical reefs (Ayal andSafriel 1982, Dulvy et al 2004).…”
Section: What Is the Role Of Time And Water Chemistry In Biological Rmentioning
confidence: 99%
“…The structure of the assemblage of intermediate consumers that link basal OM sources and higher predators can be very relevant for food web processes and ecosystem functioning. For instance, disappearance of specific intermediate consumers may result in a simplification of the food web that compromises the efficiency of energy transfers ('energetic bottlenecks', sensu Heath & Roff 1996, Sherwood et al 2002, Iles & Rasmussen 2005. The assemblage of consumers can be modulated by food availability and environmental conditions, i.e.…”
mentioning
confidence: 99%